Methodology for the process of validating qualifications in the Basque language and their adaptation to the Common European Framework of Reference for Languages (CEFR) - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Iñaki Pikabea Torrano José Francisco Lukas Mujika Universidad del País Vasco, Spain Neus Figueras Casanovas Generalitat de Catalunya, Spain   ABSTRACT In the Basque Country there are currently more than 140,000 people with accredited qualifications that certify their knowledge of Euskara (Basque Language). These qualifications have been issued by a number of official bodies dependent on the Basque Government, but had not been validated against each other until recently. In order to validate these qualifications and adapt them to the Common European Framework of Reference for Languages, a group of experts were commissioned by the Basque Government to undertake a study conducive to this end. This paper outlines the methodology and conclusions of that study.